vPaaS Model for Amateurish Users in Cloud Computing - Ying-Kun Huang; Chang-Dong Wang; De-Kai Kang; Chuan Jiang; Jian-Huang Lai (International Conference on Frontier of Computer Science and Technology (Print), 2015)
Cloud Computing manages to find its way into our daily lives. For amateurish users, most Cloud Provides such as Azure choose to rent their resources in the form of Virtual Machine (VM). However, it's not user-friendly as users have no idea about which configuration they should choose. On the other hand, users tend to have a clear idea about when to have the results. In other words, people prefer to set a "deadline" for their tasks. In this paper, we propose a novel deadline constrained model named vPaaS for amateurish cloud users. It is a mixture model combining PaaS with the idea in IaaS known as work-flow. As the name shows, we build the model referencing to the currently hot PaaS model but not exactly as it is. A more reasonable pricing model is established and the work-flow based idea is applied into our model. It's a user friendly framework with three steps in completing a task, which is able to get the result of the task before deadline.